2016
DOI: 10.3349/ymj.2016.57.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Concomitance of P-gp/LRP Expression with EGFR Mutations in Exons 19 and 21 in Non-Small Cell Lung Cancers

Abstract: PurposeTraditional chemotherapy is the main adjuvant therapy for the treatment of non-small cell lung cancer (NSCLC). However, the emergence of multi-drug resistance (MDR) has greatly restricted the curative effect of chemotherapy. Therefore, it is necessary to find a method to treat MDR NSCLC clinically. It is worth investigating whether NSCLCs that are resistant to traditional chemotherapy can be effectively treated with tyrosine kinase inhibitors targeting epidermal growth factor receptor (EGFR).Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The mechanism of drug resistance in lung cancer is very complex, and many factors are involved. First, studies identified mechanisms associated with membrane-transport protein-mediated drug efflux pumps and associated with upregulation of membrane proteins with efflux functions, such as P-glycoprotein, MRP and LRP (38,40). Second, abnormal activation of intracellular enzyme systems, such as topoisomerase (Topo) and glutamyl transpeptidase, can combine with various chemotherapeutic drug, such as platinum compounds, melphalan, cyclophosphamide, chlorambucil, doxorubicin and nitrogen mustards to reduce their activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of drug resistance in lung cancer is very complex, and many factors are involved. First, studies identified mechanisms associated with membrane-transport protein-mediated drug efflux pumps and associated with upregulation of membrane proteins with efflux functions, such as P-glycoprotein, MRP and LRP (38,40). Second, abnormal activation of intracellular enzyme systems, such as topoisomerase (Topo) and glutamyl transpeptidase, can combine with various chemotherapeutic drug, such as platinum compounds, melphalan, cyclophosphamide, chlorambucil, doxorubicin and nitrogen mustards to reduce their activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…ARS-1620, another newly developed mutant-specific inhibitor of KRAS-G12C, has a strong inhibitory effect on KRAS-G12C mutant tumors ( Molina-Arcas et al, 2019 ). At the same time, the overexpression of the ABC transporter is one of the causes of MDR in tumor cells leading to chemotherapy failure, and while the relationship between ABC expression level and KRAS mutation in cancer cells can be confirmed ( Mohelnikova-Duchonova et al, 2013 ; Wei et al, 2016 ), the relationship between the expression level of ABC transporters and KRAS inhibitor is not clear, and the effect of ARS-1620 on ABCB1-mediated MDR has not been studied yet. Therefore, we investigated the potential interaction of ABCB1 with ARS-1620.…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable research regarding the relationship of expression levels of ABC transporters with KRAS mutations in cancer cells ( Mohelnikova-Duchonova et al, 2013 ; Wei et al, 2016 ), while the link between the level of ABC transporters and KRAS inhibitors is poorly understood. In this study, we investigated the connection between novel emerged KRAS-G12C inhibitor, ARS-1620, and ABCB1-overexpressing cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…MDR1/P-gp expression is mainly mediated by alkylating agents (21). LRP serves an important role in various tumors, including gastric cancer and non-small cell lung cancer, with drug resistance (22,23). Its increased expression can mainly make tumor cells resistant to cisplatin (24).…”
Section: Discussionmentioning
confidence: 99%